Interdependence between Logistics Activities and Information Communication Technologies (ICT) - Evelin Vatovec Krmac (Promet - Traffic&Transportation, 1970)
With the growing trend toward the use of intema tiona/ supplychains and e-commerce, logistics service providers for productwarehousing, transportation and delivery are placinggreater emphasis on infomwtion communication technologies(ICT) in order to remain competitive globally. In the last decades,innovative ICT have deeply affected the way business ispeJformed and the way that organizations compete. Innovationsin electronic commerce play a key role in managinginter-organizational networks of supply chain members. Theintemet represents a powerful technology for commerce andcommunication between supply chain participants as well as atechnique for the improvement of supply chain management.But there are still some barriers that prevent the use of ICT insupply chains and consequently the ability to utilize all potentialICT advantages.